Q: What is (-2g plus 7)-(g plus 11) in it's simplest form?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

9g7+3

-3fg and -fg are like terms.

2g*(2g)2 = (2g)3 = 8g32g*(2g)2 = (2g)3 = 8g32g*(2g)2 = (2g)3 = 8g32g*(2g)2 = (2g)3 = 8g3

The answer to 2 G take away 11 times 7 equals 37. This is a math problem.

9g-14=2g 7g=14 g=2

Related questions

3 + 2g is the simplest solution without more information.

Start with your equation -2g + 11 = -21 Multiply all terms by -1 to get 2g - 11 = 21 Add 11 to both sides to get 2g = 32 Divide both sides by 2 to get g = 16

It is: 950g to 1900g or 1g to 2g in its simplest form

2g + 5h

-3g+6+2g=15 -g=9 g=-9

6g

12g

13.071 g

9g7+3

If: 2g+3 = 4 Then: g = 1/2 or 0.5

14g + 7

27-g = 2g+12 -3g = -15 g = 5